(3GdOQQ GdeMehdI aj GdgOjI GdebHhdI aj Mdd GdWH GdeTehdIs - (3CMeO Hf UGdM Hf EHQGgje Hf YHO GdeDef GdTGhj CUdG, GdOQYj CHh GdYHGS, GdCcJGhj, (B1147 (3g` s
(3ChdgG (B:s
(3hHYO aEf Yde GdWH ef egeGJ GdYdhe s
(3BNQgG (B:s
(3hgfG GfJgi HMhd Gddg hbhJg cJGH GdOQQ GdeMehdI ai GdgOjI GdebHhdI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B351s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B89 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs